Operational Best Practices in Business Ethics: A Practical and Systematic Benchmarking Tool. (June 2015) - Collins, Denis
Abstract This article describes a benchmarking tool managers can use to determine operational policies and processes that could enhance an organization's social and ethical performance. The benchmarking tool consists of a 13‐dimension, 110‐item survey based on an Optimal Ethics Systems Model. These best practices in business ethics are derived from an analysis and assessment of seven institutional infrastructures and accountability standards developed to help managers improve organizational social and ethical performance.